1991
DOI: 10.1063/1.460303
|View full text |Cite
|
Sign up to set email alerts
|

Spectra of dangling OH groups at ice cluster surfaces and within pores of amorphous ice

Abstract: Probing icy surfaces with the danglingOHmode absorption: Large ice clusters and microporous amorphous ice J. Chem. Phys. 95, 1378 (1991); 10.1063/1.461119 Spectra of dangling OH bonds in amorphous ice: Assignment to 2 and 3coordinated surface molecules J. Chem. Phys. 94, 4091 (1991); 10.1063/1.460638The OH stretching region infrared spectra of low density amorphous solid water and polycrystalline ice Ih

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
114
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(127 citation statements)
references
References 10 publications
13
114
0
Order By: Relevance
“…The spectral assignments are consistent with those made for a thin NCI film. 15,16,26 The observed spectrum (Figure 1a) also closely resembles the transmission spectrum of a liquid water film at room temperature (with the exception of the OH dangling-bond feature at 3696 cm -1 ), which further confirms the amorphous nature of the ice film. 27 Figure 1 also shows the spectral evolution of the NCI film upon annealing to 160 K. In particular, the bulk OH stretching feature appears as a sharp peak at 3238 cm -1 , while the intensities of the bulk HOH bending modes (at 1656 cm -1 ) and the OH dangling-bond mode (at 3696 cm -1 ) are found to decrease ( Figure 1e).…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…The spectral assignments are consistent with those made for a thin NCI film. 15,16,26 The observed spectrum (Figure 1a) also closely resembles the transmission spectrum of a liquid water film at room temperature (with the exception of the OH dangling-bond feature at 3696 cm -1 ), which further confirms the amorphous nature of the ice film. 27 Figure 1 also shows the spectral evolution of the NCI film upon annealing to 160 K. In particular, the bulk OH stretching feature appears as a sharp peak at 3238 cm -1 , while the intensities of the bulk HOH bending modes (at 1656 cm -1 ) and the OH dangling-bond mode (at 3696 cm -1 ) are found to decrease ( Figure 1e).…”
Section: Methodssupporting
confidence: 58%
“…Devlin and co-workers have shown that these sites give rise to two IR bands at 3720 and 3696 cm -1 , corresponding to doubly coordinated and triply coordinated water molecules, respectively. 15, 16 These OH dangling-bond features are found to be very weak in comparison to the OH stretch feature of bulk ice (3800-2800 cm -1 ) and are sensitive to the types of interactions with other molecules. For example, the study of the adsorption of hydrogen and nitrogen on NCI by Rowland et al has revealed red shifts of 10 cm -1 in these dangling-bond features for doubly coordinated and triply coordinated adsorption sites.…”
Section: Introductionmentioning
confidence: 98%
“…[13][14][15][16][17] These studies have shown that condensation of water vapor on a cold substrate at low pressure may lead to, depending upon the deposition conditions, the formation of different noncrystalline structures below 130 K and of polycrystalline ice (pc-ice) polymorphs, Ic (cubic ice), and Ih (hexagonal ice), at a more elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, IR spectroscopy, with and without the grazingangle RA technique, has been applied successfully to study the surface properties of microclusters and vapor-deposited ice films. Transmittance IR measurements of low-temperature (10-15 K) amorphous microclusters of H 2 O and D 2 O, together with molecular dynamic simulations of their surfaces, by Devlin and co-workers [15][16][17] have shown that the external and internal surfaces of these materials contain two-and three-coordinated water molecules. Part of these molecules have a noncompensated OH db, whereas others have an oxygen atom as a noncompensated site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation